Degradation of contaminants of emerging concern in a secondary effluent using synthesized MOF-derived photoanodes: A comparative study between photo-, electro- and photoelectrocatalysis - Candia-Onfray, Christian; Irikura, Kallyni [UNESP]; Calzadilla, Wendy; Rojas, Susana; Boldrin Zanoni, Maria Valnice [UNESP]; Salazar, Ricardo (Elsevier, 2023)
Three metal-organic framework (MOF)-based photoanodes were prepared by deposition on TiO2 nanotubes using Ti as substrate (Ti/TiO2NT): i) Ti/TiO2NT-Au@ZIF-8, ii) Ti/TiO2NT-Ru3(BTC)2, iii) Ti/TiO2NT-UiO-66(Zr)NH2. These photoanodes were characterized by FEG-SEM, EDX and DRX. The analyses showed a successful modification and a high homogeneity of the different MOFs on the Ti/TiO2NT surface. The photoanodes were studied in the degradation of Contaminants of Emerging Concern (CECs) in a spiked secondary effluent from a Municipal Wastewater Treatment Plant (MWWTP). Sodium diclofenac (DCF), sulfamethazine (SMT) and carbamazepine (CBZ) were used as CECs at low concentration (200 μg/L each CEC). The samples were preconcentrated using Solid Phase Extraction (SPE) and analyzed by a HPLC-DAD system. The MOF-based photoanodes exhibited a high photoelectrochemical (PEC) activity towards the oxidation of CECs, achieving up to 50%, 70% and 80% of removal using Ti/TiO2NT-Au@ZIF-8, Ti/TiO2NT-UiO-66(Zr)NH2, Ti/TiO2NT-Ru3(BTC), respectively. The influence of the generation of hydroxyl radical was then studied. The results indicate that PEC degradation using Ti/TiO2NT-Ru3(BTC)2 and Ti/TiO2NT-UiO-66(Zr)NH2 is more affected by the concentration of the radical.
Keywords: Contaminants of emerging concern; Hydroxyl radical; MOF-Derived photoanode; Photoelectrochemical degradation; Secondary effluent